1984
DOI: 10.1159/000145857
|View full text |Cite
|
Sign up to set email alerts
|

Some New Findings about Hofbauer Cells in the Chorionic Villi of the Human Placenta

Abstract: The cytological structure of the Hofbauer cells was investigated in human placentas of the first and second trimesters of gestation. These cells are found in the stromal channel system of the chorionic villi core. Their walls, which are supported by collagen fiber bundles, are produced by reticulum cells and fibroblasts. The cytoplasmic processes of the Hofbauer cells are in contact with the walls of the channels without being associated with them by desmosomal complexes. Some of these cells have features in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 21 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Since at that stage no infiltration of fetal vessels and blood into the placenta has taken place, the progenitor cells are directly derived from placental mesenchymal cells [11] rather than originating from fetal blood cells. Only slightly later placental macrophages (Hofbauer cells) appear inside the villous core in direct vicinity to the vasculogenic precursor cells indicating a putative paracrine role for these cells during the early stages of placental vasculogenesis [12]. The expression patterns of angiogenic growth factors have been described mostly for later stages of pregnancy, including acidic and basic fibroblast growth factor (aFGF, bFGF) [13,14], VEGF [15--17], and placental growth factor (PlGF) [18--20].…”
Section: Early Villous Vasculogenesismentioning
confidence: 99%
“…Since at that stage no infiltration of fetal vessels and blood into the placenta has taken place, the progenitor cells are directly derived from placental mesenchymal cells [11] rather than originating from fetal blood cells. Only slightly later placental macrophages (Hofbauer cells) appear inside the villous core in direct vicinity to the vasculogenic precursor cells indicating a putative paracrine role for these cells during the early stages of placental vasculogenesis [12]. The expression patterns of angiogenic growth factors have been described mostly for later stages of pregnancy, including acidic and basic fibroblast growth factor (aFGF, bFGF) [13,14], VEGF [15--17], and placental growth factor (PlGF) [18--20].…”
Section: Early Villous Vasculogenesismentioning
confidence: 99%
“…Early studies had already found that the most striking aspects of HBCs are their highly vacuolated appearance and their granulated cytoplasm 2 . Later investigations have pointed out that HBCs are characterized by numerous membrane-bound, electron-lucent vacuoles of different sizes, possessing amorphous material of varying density, dense granules (presumably lysosomes), and short profiles of endoplasmic reticulum 1,[3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been supported that in placentas from uncomplicated pregnancies, HBCs either disappear or become scanty after the fourth to fifth month of gestation. On the other hand, in cases of pathological placentas due to intrauterine growth restriction (IUGR) or gestational diabetes mellitus their density seems to be increased 4,6,9 . However, electron microscopy studies and immunohistochemistry demonstrated their presence throughout normal uncomplicated pregnancy as well, until term, and not only in immature villi of the center of the placentone.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the early appearance of macrophages (Hofbauer cells) in the villous core which have been affected the villous vascularisation (Demir and Erbengi, 1984) and described to regulate distinct trophoblast functions (Cervar et al, 1999) and to express angiogenic growth factors (VEGF) (Demir et al, 2004), suggests a paracrine role for these cells during the first stages of vasculogenesis (Demir et al, 1997;Seval et al, 2007).…”
Section: Introductionmentioning
confidence: 99%